Study of safety and health aspects of base stations and mobile phones - Kasumawati, Lias. (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The wide use of mobile phones and also the increasing number of base stations have inevitably raised the question of whether there are any implications for human health. This project focused on study of safety and health aspects of mobile phones and base stations. Much attention is paid to the effect of mobile phones rather than base stations. There are four conditions taking into consideration for this project. First, mobile phone held next to human head, second, loudspeaker and third Bluetooth conditions. Last and forth condition is focused on base stations effects on human health.For the assessment purpose, Finite Difference Time Domain (FDTD) is used in order to find the Specific Absorption Rate (SAR) rating or values of four conditions that have been mentioned. International Commission on Non-Ionizing Radiation Protection(ICNIRP) has been stated the limits of SAR which is 4W/kg. When the limits is exceed,it produces human health effects where it can caused reverse cell membrane polarity,alter brainwaves and brain chemistry and damage DNA. This leads to cancer and memory loss. However, both mobile phone and base stations are designed with low power and operate at high frequency where the value of SAR is low than the limits that stated by ICNIRP. Other temporary biological effects produce by mobile and basestations are heating, headache, fuzziness, fatigue and nausea. As a conclusion, there is still no convinced evidence that mobile phone and base stations caused human adversehealth effect and shorten human life span.